role of transmural ventricular heterogeneities in cardiac vulnerability to electric shocks - Maharaj, T; Blake, R; Trayanova, N; Gavaghan, D; Rodriguez, B (2015)
Transmural electrophysiological heterogeneities have been shown to contribute to arrhythmia. induction in the heart; however, their role in defibrillation failure has never been examined. The goal of this study is to investigate how transmural heterogeneities in ionic currents and gap-junctional coupling contribute to arrhythmia generation following defibrillation strength shocks. This study used a 3D anatomi